THE CORRELATION BETWEEN STUDENTS’ SELF-ESTEEM AND SPEAKING PERFORMANCE - Willieana Bernadet; Luwandi Suhartono; Urai Salam (Universitas Tanjungpura, 2021)
AbstractThis research was aimed to describe the correlation between students’ selfesteem and speaking performance. This research was conducted due to the fact that many students in English Education Study Program of FKIP UNTAN faced the speaking problem. This problem was mainly caused by students’ less confidence on their speaking ability. This research applied the correlational design. This research worked with students in Batch 2016. The techniques used for data collection were interview and measurement, while the tools were questionnaire and interview guide. The findings revealed that the correlation coefficient between self-esteem and speaking performance was 0.4. This indicated that these two variables had moderate correlation. Thus, there was a correlation between students’ self-esteem and speaking performance.Keywords: Correlational Study, Self-esteem, Speaking Performance